Single-Incision Single-Instrument Adnexal Surgery in Pediatric Patients. (7th October 2015) - Loux, Tara; Falk, Gavin A.; Gaffley, Michaela; Ortega, Stephanie; Ramos, Carmen; Malvezzi, Leopoldo; Knight, Colin G.; Burnweit, Cathy
Abstract : Introduction . Pediatric surgeons often practice pediatric gynecology. The single-incision single-instrument (SISI) technique used for appendectomy is applicable in gynecologic surgery. Methods . We retrospectively analyzed the records of patients undergoing pelvic surgery from 2008 to 2013. SISI utilized a 12 mm transumbilical trocar and an operating endoscope. The adnexa can be detorsed intracorporeally or extracorporealized via the umbilicus for lesion removal. Results . We performed 271 ovarian or paraovarian surgeries in 258 patients. In 147 (54%), the initial approach was SISI; 75 cases (51%) were completed in patients aged from 1 day to 19.9 years and weighing 4.7 to 117 kg. Conversion to standard laparoscopy was due to contralateral oophoropexy, solid mass, inability to mobilize the adnexa, large mass, bleeding, adhesions, or better visualization. When SISI surgery was converted to Pfannenstiel, the principal reason was a solid mass. SISI surgery was significantly shorter than standard laparoscopy. There were no major complications and the overall cohort had an 11% minor complication rate. Conclusion . SISI adnexal surgery is safe, quick, inexpensive, and effective in pediatric patients. SISI was successful in over half the patients in whom it was attempted and offers a scarless result. If unsuccessful, the majority of cases can be completed with standard multiport laparoscopy.